2020
DOI: 10.3390/microorganisms8101526
|View full text |Cite
|
Sign up to set email alerts
|

A New Endemic of Concomitant Nonalcoholic Fatty Liver Disease and Chronic Hepatitis B

Abstract: Hepatitis B virus (HBV) infection remains a global public problem despite the availability of an effective vaccine. In the past decades, nonalcoholic fatty liver disease (NAFLD) has surpassed HBV as the most common cause of chronic liver disease worldwide. The prevalence of concomitant chronic hepatitis B (CHB) and NAFLD thus reaches endemic proportions in geographic regions where both conditions are common. Patients with CHB and NAFLD are at increased risk of liver disease progression to cirrhosis and hepatoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 160 publications
(208 reference statements)
0
5
0
Order By: Relevance
“…Hepatitis B virus (HBV) infection is a significant cause of cirrhosis, hepatocellular carcinoma (HCC), grave morbidity, and mortality (1). Globally, it is estimated that 240 to 350 million of the world's population has hepatitis B (2).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) infection is a significant cause of cirrhosis, hepatocellular carcinoma (HCC), grave morbidity, and mortality (1). Globally, it is estimated that 240 to 350 million of the world's population has hepatitis B (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, according to a recent East Asia expert opinion, liver biopsies for all such patients are unrealistic and may also not distinctly pinpoint the exact cause leading to ALT elevation [ 16 ]. Additionally, there are no specific recommendations for antiviral therapy among exclusively patients with coexisting CHB and NAFLD by current practice guidelines [ 16 , 17 ]. This conundrum poses a dilemma for clinicians regarding the management or treatment initiation of this special population in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Coexistence of NAFLD and CHB is commonly observed in high HBV‐endemic regions. 2 A meta‐analysis reported that the prevalence of hepatic steatosis was about 25%–30% among patients with CHB. 3 Previous studies reported that concomitant presence of HBV and hepatic steatosis is associated with increased risk of disease progression to cirrhosis and hepatic and extrahepatic malignancies, 4 , 5 as Choi et al 6 reported that patients with CHB and nonalcoholic steatohepatitis (NASH) had higher liver‐related outcomes and overall mortality than those with CHB alone.…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of living conditions and lifestyle changes, the incidence rate of nonalcoholic fatty liver disease (NAFLD) is increasing. Coexistence of NAFLD and CHB is commonly observed in high HBV‐endemic regions 2 . A meta‐analysis reported that the prevalence of hepatic steatosis was about 25%–30% among patients with CHB 3 .…”
Section: Introductionmentioning
confidence: 99%